Simulation and modeling of turbulent flows - Gatski, T. B.; Hussaini, M. Yousuff; Lumley, John L. 1930-2015 (Oxford University Press, 1996)
This book provides students and researchers in fluid engineering with an up-to-date overview of turbulent flow research in the areas of simulation and modeling. A key element of the book is the systematic, rational development of turbulence closure models and related aspects of modern turbulent flow theory and prediction. Starting with a review of the spectral dynamics of homogenous and inhomogeneous turbulent flows, succeeding chapters deal with numerical simulation techniques, renormalization group methods and turbulent closure modeling. Each chapter is authored by recognized leaders in thei.
Keywords: Turbulence -- Mathematical models.; Fluid dynamics.; elektronické knihy; electronic books